SEKTOR PETANIAN DAN PERTUMBUHAN EKONOMI DI KABUPATEN ACEH BESAR - Alfani, Syafiqurrahman; Zulkifli, Zulkifli (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
AbstractThis study aims to analyze the agricultural sector and economic growth in a large Aceh district. The data used in this study is a series of time (time series) and are quantitative (Gujarati, 2006). The method used is Location Quotient, sampling using data from the Central Statistics Agency. The agriculture sub-sector is the base sector in Aceh Besar because it is from 2011-2016 that the agriculture sub-sector is higher than one. Where according to the model of the Location Quotient (LQ) if the number generated is greater than one then the subsector is base, then from this the agriculture subsector is the base subsector, while the forestry and fisheries subsector is the non-base subsector. The agricultural sector is very important in a large Aceh district therefore the government must take part in developing the agricultural sector one way to develop the agricultural sector is, by means of more support to make agro-tourism or agro-industry that can process and regulate the output of the sector.Keywords: Agriculture sector, Economic Growth, Gross Domestic Regional Product (GDRP), Location Quatient (LQ).